Long-term prognostic value of ischaemia and cardiovascular magnetic resonance-related revascularization for stable coronary disease, irrespective of patient's sex: a large retrospective study. (20th September 2021) - Pezel, Théo; Garot, Philippe; Kinnel, Marine; Hovasse, Thomas; Champagne, Stéphane; Sanguineti, Francesca; Toupin, Solenn; Unterseeh, Thierry; Garot, Jérôme
Abstract: Aims: To assess the sex-specific, long-term prognostic value of myocardial ischaemia induced by stress cardiovascular magnetic resonance (CMR) and early CMR-related revascularization in consecutive patients from a large registry. Methods and results: Between 2008 and 2010, all consecutive patients referred for stress CMR were followed for the occurrence of major adverse cardiovascular events (MACE), defined by cardiovascular mortality or recurrent non-fatal myocardial infarction (MI). Early CMR-related revascularization was defined as any revascularization within 90 days after CMR. Among 3664 patients (56.9% male, mean age 69.9 ± 11.8 years), 472 (12.9%) had MACE (163 women and 309 men) after a median follow-up of 8.8 (IQR 6.9-9.5) years. Inducible ischaemia and late gadolinium enhancement (LGE) by CMR were associated with MACE in women and men (all P  < 0.001). In multivariable Cox regression, inducible ischaemia, LGE, and CMR-related revascularization were independent predictors of MACE both in women [heart rate (HR) 4.79, 95% confidence interval (CI) 2.17–9.10; HR 1.82, 95% CI 1.22–2.71; HR 0.71, 95% CI 0.54–0.92, respectively; all P  < 0.001] and men (HR 3.88, 95% CI 2.33–5.98; HR 1.48, 95% CI 1.16–1.89; HR 0.78, 95% CI 0.65–0.97, respectively; all P  < 0.001). The addition of CMR-parameters led to improved model discrimination for MACE (C-statistic 0.61 vs. 0.71; NRI = 0.212; IDI = 0.032) for both women and men. CMR-related revascularization was associated with a lower incidence of MACE in patients with left ventricular ejection fraction (LVEF)<50%. Conclusion: Inducible ischaemia and early CMR-related revascularization were good long-term predictors of MACE irrespective of sex. CMR-related revascularization was associated with a lower MACE incidence in the sole sub-set of patients with LVEF < 50%.